A Vertically Integrated Pathway for Infusing Engineering Technicians with Industrial Cybersecurity Competencies (Journal of The Colloquium for Information Systems Security Education, 2022)
This paper describes an effort to establish a vertically integrated pathway to identify and develop industrial control systems cybersecurity talent that extends from middle school to graduate degrees, leveraging the unique strengths of career and technical education. Educators and administrators seeking to ignite student interest in cybersecurity at a young age, and to provide a clear curriculum pathway to meet employer needs in the field of industrial cybersecurity may find this effort of use.
Keywords: industrial control systems; cybersecurity; training; education; career and technical education; engineering technology; technicians